Fulfillment of the Right of Access to Justice Through the Application of Restorative Justice Principles for Women Facing the Law - Undang Abdul Mutolib; Nanun Abdillah; Asep Irfan; Imam Sucipto; Mujio Nurkholis (Yayasan Mentari Madani, 2023)
The right to obtain justice is a human right that must be respected, protected, and fulfilled by the state.